Schelling's substantive reinterpretation of the transcendental turn: beyond method. Issue 2 (4th March 2019) - Gardner, Sebastian
ABSTRACT: Several factors, including but not limited to his investments in Naturphilosophie and Spinoza, make it hard to determine the extent to which Schelling remains on track with Kant's transcendental project. My aim here is to isolate Schelling's conception of transcendental method in the first decade of his philosophical development, a topic that has received little direct and extended discussion. Schelling's 1800 System of Transcendental Idealism stands out as of particular importance, but no single text can be regarded as Schelling's definitive statement of his views on the question of method in his early period, necessitating a diachronic approach. I argue that, though in important respects Schelling's concerns diverge from those of Kant and Fichte, Schelling should not be regarded as abandoning the transcendental framework, and is best understood as attempting to work out what is involved at the original point of adoption of the transcendental standpoint. This entails, I argue, exchanging transcendental philosophy's claim to a distinctive method for a substantive interpretation of the transcendental turn.